Motherhood - Edelbaum, Jana.; Dieckmann, Katherine; Edwards, Anthony, 1962-; Thurman, Uma.; Driver, Minnie; E1 Entertainment (Firm); iDeal Partners; Killer Films; 120db Films (Port Washington, NY : E1 Entertainment, 2009)
A stay-at-home mother tries to plan her daughter's birthday party, help her absent-minded husband, make up with her best friend, and still have time to write a large essay for a contest in a major magazine.
Originally released as a motion picture in 2009.
Special features: Interviews with Uma Thurman, Anthony Edwards, Minnie Driver and Katherine Dieckmann; audio commentary with Katherine Dieckmann and Rachel Cohen.
Music, John Henry.
Anthony Edwards, Uma Thurman, Minnie Driver.
Rating: PG-13; for language, sexual references and a brief drug comment.
DVD; Dolby Digital 5.1 surround; Dolby Digital 2.0; 16x9 (1.78:1).
Keywords: Motherhood -- Drama; Stay-at-home mothers -- Drama; Interpersonal relations -- Drama; Maternidad -- Teatro; Relaciones humanas -- Teatro; Comedy films; Feature films; Fiction films; Video recordings for the hearing impaired